Harvest managements and cultural practices in sugarcane - Castro, Sérgio Gustavo Quassi De; Franco, Henrique Coutinho Junqueira; Mutton, Miguel Ângelo [UNESP] (Sociedade Brasileira de Ciência do Solo, 2014)
The presence of trash from the mechanical harvest of green cane on sugarcane plantations promotes changes in the agricultural management, for example, in the mechanical cultural practices of ratoon cane in-between the rows and nitrogen (N) fertilization. The goal of this study was to evaluate the performance of sugarcane in different harvest systems, associated to the mechanical cultural practices in interrows and N rates. The study was carried out on a sugarcane plantation in Sales Oliveira, São Paulo, Brazil, with the sugarcane variety SP81-3250, on soil classified as Acrudox, in a randomized block design with split-split plots and four replications. The main treatments consisted of harvest systems (harvesting green cane or burnt cane), the secondary treatment consisted of the mechanical cultural practices in the interrows and the tertiary treatments were N rates (0, 30, 60, 90, 120 and 160 kg ha-1), using ammonium nitrate (33 % N) as N source. The harvest systems did not differ in sugarcane yield (tons of cane per hectare - TCH), but in burnt cane, the pol percent and total sugar recovery (TSR) were higher. This could be explained by the higher quantity of plant impurities in the harvested raw material in the system without burning, which reduces the processing quality. Mechanical cultural practices in the interrows after harvest had no effect on cane yield and sugar quality, indicating that this operation can be omitted in areas with mechanical harvesting. The application of N fertilizer at rates of 88 and 144 kg ha-1 N, respectively, increased stalk height and TCH quadratically to the highest values for these variables. For the sugar yield per hectare (in pol %), N fertilization induced a linear increase.

A presença da palha no campo, oriunda da colheita mecanizada sem despalha a fogo, implica em mudanças no manejo da cana-de-açúcar, como na realização do cultivo mecânico da soqueira e na fertilização nitrogenada. O objetivo deste trabalho foi avaliar o desenvolvimento da cana-de-açúcar submetida aos diferentes sistemas de colheita, associado à realização ou não do cultivo mecânico, e à aplicação de doses de nitrogênio (N). O trabalho foi desenvolvido na região de Sales Oliveira, SP, em área comercial de cana-de-açúcar, com a variedade SP81-3250 (2º corte), em um Latossolo Vermelho acriférrico. O delineamento foi em blocos casualizados com parcelas subsubdivididas, em quatro repetições, em que os tratamentos principais eram os sistemas de colheita (cana crua ou cana queimada); os tratamentos secundários à realização ou não do cultivo mecânico; e os tratamentos terciários às doses de N (0, 30, 60, 90, 120 e 160 kg ha-1), usando como fonte o nitrato de amônio (33 % N). Os sistemas de colheita não diferiram para a produtividade da cana-de-açúcar (t ha-1 de cana - TCH), porém a cana queimada apresentou maior teor de sacarose (Pol) e açúcar total recuperável (ATR), sendo esse fato em razão, provavelmente, do aumento das impurezas vegetais que fazem com que a qualidade tecnológica diminua. O cultivo mecânico da soqueira após a colheita da cultura não apresentou nenhum impacto na produtividade de colmos e açúcar, indicando que essa operação pode ser desconsiderada em áreas com colheita mecânica. A aplicação de fertilizante nitrogenado aumentou a altura de colmos e TCH de forma quadrática com as doses de 88 e 144 kg ha-1 de N, proporcionando os maiores valores para essas variáveis. Para a produção de açúcar por hectare (TPH), houve aumento linear em razão da adubação nitrogenada.
Sistemas de manejo de colheita e tratos culturais na cultura da cana-de-açúcar
Keywords: Nitrogen fertilization; mechanical cultural practices; green cane; Saccharum spp.; Adubação nitrogenada; cultivo mecânico; Cana crua; Saccharum spp.